Inhibition of PDE2 and PDE4 synergistically improves memory consolidation processes. (15th February 2021) - Paes, Dean; Xie, Keqiang; Wheeler, Damian G.; Zook, Douglas; Prickaerts, Jos; Peters, Marco
Abstract: Phosphodiesterases (PDE) are the only enzymes that degrade cAMP and cGMP which are second messengers crucial to memory consolidation. Different PDE inhibitors have been developed and tested for their memory-enhancing potential, but the occurrence of side effects has hampered clinical progression. As separate inhibition of the PDE2 and PDE4 enzyme family has been shown to enhance memory, we investigated whether concurrent treatment with a PDE2 and PDE4 inhibitor can have synergistic effects on memory consolidation processes. We found that combined administration of PF-999 (PDE2 inhibitor) and roflumilast (PDE4 inhibitor) increases the phosphorylation of the AMPA receptor subunit GluR1 and induces CRE-mediated gene expression. Moreover, when combined sub-effective and effective doses of PF-999 and roflumilast were administered after learning, time-dependent forgetting was abolished in an object location memory task. Pharmacokinetic assessment indicated that combined treatment does not alter exposure of the individual compounds. Taken together, these findings suggest that combined PDE2 and PDE4 inhibition has synergistic effects on memory consolidation processes at sub-effective doses, which could therefore provide a therapeutic strategy with an improved safety profile. Highlights: Phosphodiesterases are candidate targets for cognitive enhancement. PDE4 and PDE2 regulate processes of memory consolidation, but PDE4 is associated with side-effects limiting its clinical utility. Combining selective inhibitors of PDE2 and PDE4 broadens the efficacious dose range with efficacy at lower doses. PDE2+4 dual inhibition exerts synergistic effects on memory, CRE-mediated gene-expression, and GluR1 Ser845 phosphorylation. Our results suggest that drugs targeting both PDE2 and PDE4 may yield superior efficacy over selective inhibitors.